Morphology and Molecular Identification of Cyprinidae from the Sumber Umbulan Ngenep, Malang Regency, East Java - Naya Rabbani, Calista; Damayanti, Ayu Elysia; Tresna Sulung, Cahya Ajeng Valenta; Rahayu, M.Si, Dwi Anggorowati; Nugroho, Endik Deni; Rusdianto, Rusdianto; Binti Mamat, Noorhidayah (Jurnal Riset Biologi dan Aplikasinya, 2025)
The genus Tor comprises freshwater fish belonging to the Cyprinidae family, recognized for their remarkable diversity and broad distribution across Southeast Asia, including Indonesia. Despite this, data on Tor species in certain regions are limited, highlighting the need for additional research to confirm their presence. Therefore, this study aims to examine the genetic diversity and phylogenetic reconstruction of the species observed in Sumber Umbulan Ngenep using the COI gene as a DNA barcode marker. The research was conducting using the Purposive Random Sampling method and fin tissues were preserved in 96% ethanol for DNA analysis. The species found at Sumber Umbulan Ngenep were observed morphologically using a phenetic approach. Fins from each fish sample were collected and subjected to PCR, sequence analysis using the BOLD System, phylogenetic tree reconstruction, ABGD analysis, and QR barcoding. The results of morphological, genetic, and phylogenetic tree reconstruction based on the COI gene indicate that three species have been identified at Sumber Umbulan Ngenep, namely Tor douronensis, Tor tambra, and Barbonymus gonionotus. Based on the phenetic approach, three apomorphies and five automorphies were identified, indicating the relatedness of the observed species with the reference species. The phylogenetic tree topology shows an unambiguous branching pattern for the observed sample cluster with Poecilia reticulata as the outgroup. This study is the first to identify the species present at Sumber Umbulan Ngenep, Malang Regency, East Java, Indonesia. The findings provide new information about the existence of these species and can serve as a basis for future conservation and management strategies.